Review: MARCO GIUMAN, La trottola nel mondo classico, (Quaderni di Otium, 4), Giorgio Bretschneider Editore, 2020 (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Marco Giuman’s essay follows a renewed interest in childhood and play in the Classical world, which has crossed several research fields in recent years. By carefully analyzing archaeological and textual evidence, Giuman reconstructs for the spinning top a complex involvement within a symbolic and ritual dimension, far beyond its most elementary ludic connotations.
Keywords: spinning top; game; childhood; rituality